Heavy metal toxicity in poultry: a comprehensive review - Aljohani, Abdullah S. M. (Frontiers in Veterinary Science, 2023)
Arsenic (As), lead (Pb), cadmium (Cd) and mercury (Hg) have been recognized as most toxic heavy metals which are continuously released into environment through natural sources and anthropogenic fertilizers production, industrial activities and waste disposal. Therefore As, Cd, Hg and Pb concentrations increase in water bodies, fodders, feed and tissues of livestock including poultry in the surrounding of industrial areas, leading to metabolic, structural and functional abnormalities in various organs in all animals. In poultry, bioaccumulation of As, Pb, Cd and Hg occurs in many organs mainly in kidney, liver, reproductive organs and lungs due to continuous exposure of heavy metals. Consumption of Cd lowers the efficiency of feed conversion, egg production and growth in poultry. Chronic exposure of As, Pb, Cd and Hg at low doses can change the microscopic structure of tissues mainly in brain, liver, kidney and reproductive organs due to increase contents in these tissues. The histopathological changes in kidney, liver and reproductive organs are negatively reflected in enzyme activity and serum biochemical parameters. Metals toxicity is determined by route of exposure, length of exposure and absorbed dosage whether chronic and acute. The current review discusses about the As, Cd, Pb and Hg bioaccumulation and histopathological changes in different tissues and toxic concentrations of As, Cd, Pb and Hg in poultry.